Шитье и рукоделие : энциклопедия - Андреева И. А. (Большая Российская энциклопедия, 2000)
Экземпляры: ф.16 (20190325) / Инвентарный номер: 046800 / Цена: 39.00 / Авт.знак: Ш 64 / ГРНТИ: 75.35 / ББК: 37.248я2